Labor Force Participation and Earnings in a Demographic Model of the Labor Market - Toikka, Richard S.; Holt, Charles C. (American Economic Review, 1976)
A structural model of the labor market should improve our understanding of and ability to predict unemployment and wage change. With such a model of the labor market and the inflation process we should be better able to prescribe policies for aggregate demand and for structural improvements that are designed to reduce inflation and unemployment. Because labor market dynamics are fast, the duration of unemployment being only a few months, a structural model to reflect turnover and search behavior must have a very short period-a quarter would be too long. However, since real wages change sluggishly, the usual allocation variables will not be fully effective in regulating the turnover and search behavior of workers and employers. Hence, we expect that the short-term dynamics of the labor market will be regulated primarily by the availability in the market of jobs and workers. The composition of unemployment shows wide disparities for different demographic groups which suggests the desirability of separately estimating their search and turnover behaviors.